Muhammed b. Yusuf el-Hanbeli et-Tazifi ve Rabtu'ş-şevarid fi halli'ş-şevahid adlı eserinin edisyon kritiği - Aliibrahim, Hussein Alhasan (My University, 2018)
Zincânî'nin Tasrifu’l-İzzî adlı eseri sarf ilminin önemli kitaplarından birisi olarak kabul edilir. Eser uzun süre bir ders kitabı olarak okutulmuş ve üzerine şerhler yazılmıştır. Kitabın en meşhur şerhi olan Teftâzânî’nin şerhinde izaha gerek duyulan şiir beyitleri bulunmaktadır ve bundan ötürü İbnü’l-Hanbelî Rabtu’ş-Şevârid fi halli’ş-Şevâhid adlı kitabı yazmıştır. Bu çalışmayı üç bölüme ayırdık. İlk bölümde üç âlimin (İzzî, Teftâzânî, İbnü’l-Hanbelî) hayatlarına, hocalarına, talebelerine ve en önemli eserlerine yer vererek bu alimlerin tanıtımını yaptık. İkinci bölümde el yazması çalışmasına yer verdik. Bu bölümde, araştırmada incelediğim nüshanın tanıtımı, nitelikleri, özellikleri, yazılma sebebi, üslubu ve bunlara ek olarak yazarın başvurduğu kaynaklar ve yazarın bu kaynaklar arasından öncelediklerinin belirtilmesini göstermeye çalıştım.Üçüncü bölümde de metinde geçen şiirlerin hangi şairlere ait olduğu, bu kişilerin tanıtımı ve yine kitapta geçen sözlerin ait olduğu kişiler ve bu sözlerin yer aldığı kitapları içeren bir metin incelemesi yaptık.

Al-Azzi's Book of Dignity of Zanjani (655/ 1257) is considered one of theimportant books in the science of morphology. Therefore his life and his works are essential points of study. In his most famous comentary (791/ 13898) he mentioned verses of poetry that needed explanation and clarification. This why Ibn Hanbali wrote his book Linking the evidence in the solution of the evidence which we discussed in this work. We divided our work into three sections: 1.discussions on the three scientists (Al-Azi, Tafazani, Ibn Hanbali), providing information about their lives, teachers, students, and the most famous works they left us.2.Study of the manuscript. We discussed the details of a specific version of the text through its characteristics, reasons of the authorship, style, sources and references which used by the writer, and reference to the importance of the writers he cited.3.In this section we verified the authenticity of the manuscript. This was done by identifying the authors of the poems, discussing their lives, connecting the sayings mentioned with their authors and finally discussing other texts that used the poems.
Keywords: Arabic language; Arap Dili; Arap Grameri; et-Tâzifî; History; İbnu’l-Hanbelî; Linking the evidence in the solution of the evidence; Rabtu’ş-Şevârid; Retorik; Rhetoric; Sarf Ibn Hanbali; Şevâhid; Tarih; Tasrif el-Azzi; Tasrifu'l îzzî; Tazifi